Bourne supremacy - Greengrass, Paul.; Damon, Matt.; Potente, Franka, 1974-; Cox, Brian, 1946-; Stiles, Julia, 1981-; Urban, Karl, 1972-; Wood, Oliver; Powell, John, 1963-; Ludlum, Robert, 1927-2001.; Universal Pictures (Firm) (Universal City, Calif. : Universal, 2004)
Jason Bourne has abandoned his life as a CIA assassin and has been traveling beneath the agency's radar. He has been able to reconnect with Marie, the woman he loves. But Bourne is still haunted by vivid dreams and troubling memories of his days as a killer, and he's not really certain how much really happened and how much is a product of his imagination. When Bourne is led out of hiding by circumstances beyond his control, he must reconcile his past and present as he struggles to keep Marie out of harm's way and foil an international incident with dangerous consequences.
Based on the novel by Robert Ludlum.
Special features: explosive deleted scenes; matching identities: casting; keeping it real; blowing things up; on the move with Jason Bourne; Bourne to be wild: fight training; crash cam: racing through the streets of Moscow; the go-mobile revs up the action; anatomy of a scene: the explosive bridge chase scene; scoring with John Powell; feature commentary with director Paul Greengrass; cast and filmmakers; DVD-ROM features.
Matt Damon, Franka Potente, Brian Cox, Julia Stiles, Karl Urban, Gabriel Mann, Joan Allen.
DVD, region 1, full screen (1.33:1) presentation; Dolby Digital surround, dual-layer, single-sided.
Keywords: Bourne, Jason (Fictitious character); Assassins; Espionage; Feature films; Thriller; Video recordings for the hearing impaired